Corrective feedback in language learning - Basiron, Halizah; Knott, Alik; Robins, Anthony (2008)
In the language learning classroom, teachers always provide either positive evidence or negative evidence to learners in response to the learners’ erroneous sentence (Kim, 2004). The negative evidence is also known as corrective feedback. This paper describes various types of corrective feedback provided to the learners when learning a second language (L2). We also discuss how corrective feedback facilitates language learning in five stages: notice, locate, perceive, uptake and repair. We argue that the nature of corrective feedback (explicit or implicit) has some effect how the feedback works in language learning.